Human CFTR deficient iPSC-macrophages reveal impaired functional and transcriptomic response upon Pseudomonas aeruginosa infection - Rodriguez Gonzalez, Claudio; Basílio-Queirós, Débora; Neehus, Anna-Lena; Merkert, Sylvia; Tschritter, David; Ünal, Sinem; Hegermann, Jan; Mörgelin, Matthias; Bustamante, Jacinta; Nietert, Manuel Manfred; Martin, Ulrich; Tümmler, Burkhard; et al. (Frontiers in Immunology, 2024)
Cystic fibrosis (CF) is a hereditary autosomal recessive disease driven by deleterious variants of the CFTR gene, leading, among other symptoms, to increased lung infection susceptibility.Mucus accumulation in the CF lung is, as of yet, considered as one important factor contributing to its colonization by opportunistic pathogens such as Pseudomonas aeruginosa. However, in recent years evidence was provided that alveolar macrophages, which form the first line of defense against airborne pathogens, seem to be intrinsically defective with regard to bactericidal functionality in the CF lung. To assess the impact of CFTR deficiency in human macrophages only insufficient systems are available. To address this problem and to evaluate the role of CFTR in human macrophages, we successfully differentiated human induced pluripotent stem cells (iPSC) from a CF p.Phe508del homozygous individual and a healthy donor into primitive macrophages (iMac ΔF508 and iMac WT ), respectively, and compared the bactericidal functionality in the relevant cell type. iMac ΔF508 showed impaired P. aeruginosa clearance and intracellular killing capacity in comparison to iMac WT . Furthermore, iMac ΔF508 exhibited a less acidic lysosomal pH, and upon P. aeruginosa infection, there were signs of mitochondrial fragmentation and autophagosome formation together with a hyperinflammatory phenotype and deficient type I interferon response. In summary, we present a defective phenotype in iMac ΔF508 upon P. aeruginosa infection, which will constitute an ideal platform to further study the role of macrophages in the context of CF.